2010
DOI: 10.5194/acp-10-4453-2010
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and comparison of primary biological aerosol above and below a tropical forest canopy using a dual channel fluorescence spectrometer

Abstract: Original article can be found at: http://www.atmos-chem-phys.net/10/issue10.html Copyright - the authors. Authors grant any third party the right to use the article freely as long as its original authors and citation details are identified. The article and any associated published material is distributed under the Creative Commons Attribution 3.0 License.Aerosol particle size distributions were measured below and above a tropical rainforest canopy in Borneo, Malaysia, in June/July 2008 using the WIBS-3: a sing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
256
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(275 citation statements)
references
References 32 publications
(28 reference statements)
17
256
0
Order By: Relevance
“…Previously it has been reported that real-time LIF analysis enables classification of bioaerosols from other aerosols in atmosphere (Gabey et al 2010;Huffman et al 2010;Pan 2015). Our results show that combined LIF and LIBS analysis is promising tool for online classification of atmospheric bioaerosols.…”
Section: Identification Of Microbial Particlesmentioning
confidence: 49%
See 1 more Smart Citation
“…Previously it has been reported that real-time LIF analysis enables classification of bioaerosols from other aerosols in atmosphere (Gabey et al 2010;Huffman et al 2010;Pan 2015). Our results show that combined LIF and LIBS analysis is promising tool for online classification of atmospheric bioaerosols.…”
Section: Identification Of Microbial Particlesmentioning
confidence: 49%
“…Fluorescence-based online bioaerosol instruments, such as BioScout, WIBS, and UV-APS, have been used in various environments, but it is really challenging to classify different types of bioaerosols with these instruments (Gabey et al 2010;Huffman et al 2010;Saari et al 2014). It should be noted that fluorescence analysis alone may include uncertainties due to fluorescent non-biological artifacts in ambient air leading to false counts of bioaerosols (P€ ohlker et al 2012;Saari et al 2013).…”
Section: Lif Spectra Of Microbial Particlesmentioning
confidence: 99%
“…We validated the procedure using a commercially available WIBS (model 4A), first described by Kaye et al (2005) and later in significant detail by Gabey et al (2010) and Perring et al (2015). We will briefly describe its operating principles and the instrument settings used in this study.…”
Section: Wideband Integrated Bioaerosol Sensor (Wibs-4a) Operationmentioning
confidence: 99%
“…The use of these fluorescence magnitudes, however, varies widely in the published literature. Several recent studies have employed a binary yes-no classification of fluorescence above a threshold (e.g., Gabey et al, 2010;Perring et al, 2015), essentially ignoring the fluorescence magnitude beyond the threshold. Fluorescence magnitudes have been used as input variables in automated particle-clustering analyses (Robinson et al, 2013;Crawford et al, 2015) and to manually sort sampled particles into groupings (Wright et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The fully analysed bioaerosol dataset with species identification is discussed in a separate publication (Gabey et al, 2010).…”
Section: Example Field Datamentioning
confidence: 99%